Mental stress promotes the proliferation of endometriotic lesions in mice. (November 2020) - Kawakita, Takako; Kato, Takeshi; Iwasa, Takeshi; Erdenebayar, Otgontsetseg; Kadota, Yuri; Kasai, Kana; Yoshida, Kanako; Irahara, Minoru
Highlights: Mental stress promotes endometriosis. Mental stress increases levels of pro-inflammatory cytokines. Adipose-tissue inflammation is caused by mental stress. Abstract: Endometriosis is a condition in which tissue similar to the womb lining begins to grow in other sites, such as the ovaries or fallopian tubes. Endometriosis can cause pelvic pain, adhesion formation, and infertility. Here, we investigated the relationship between deterioration of endometriosis and inflammation of intraperitoneal adipose tissue in mice. We created a mouse model of endometriosis, then subjected these mice to stress loading. In the experimental mice, we measured protein expression levels of prostaglandin-E2, monocyte chemoattractant protein-1, and tumor necrosis factor-α using ELISA kits. We used quantitative real-time polymerase chain reaction to measure mRNA expression levels of inflammation-related enzymes and cytokines in lesions and adipose tissues. This study sugest that endometriotic lesions may progress in the presence of psychological stress in the presence of endometriosis. In addition, inflammation of the adipose tissue around the uterus may be involved in the development of endometriosis. However, this needs further consideration. Reducing or avoiding stress as much as possible may prevent the progression of endometriosis.